Knowledge and perception about tuberculosis among general population attending community pharmacies in Mosul: A cross-sectional study - Luma Moayad Al-Obaidy; Heba Mwaffaq Attash; Harith Khalid Al-Qazaz (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate people’s knowledge and perceptions regarding tuberculosis. Method: The cross-sectional study was conducted at 10 community pharmacies in Mosul, Iraq, from December 2021 to March 2022, and comprised individuals of either gender aged >18 years. Data was collected using a 17-item questionnaire, with 12 questions related to knowledge and 5 related to perception regarding tuberculosis. Data was analysed using SPSS 25. Results: Of the 200 participants with mean age 38.79+/-13.72 years, 113(56.5%) were females and 101(50.5%) had education up to university level. Overall, 85(42.5) subjects could differentiate between tuberculosis and pulmonary tuberculosis, and 176(88%) knew TB was curable. Besides, 135(67.5%) subjects said they would not visit patients with tuberculosis. Conclusion: The national tuberculosis control programme in Iraq seemed to have improved public awareness regarding tuberculosis. Key Words: Tuberculosis, Pulmonary